2019
DOI: 10.1177/0886260519844274
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Psychological Intimate Partner Violence Exposure and Gender Discrimination on Postnatal Mental Health Trajectories

Abstract: While the literature examining physical intimate partner violence (IPV) is extensive, the impact of psychological IPV on mental health during highrisk times such as the period following childbirth is not well understood. The current study examined associations between psychological IPV and the course and severity of women's postnatal mental health symptoms (depression, anxiety, and trauma symptoms). Both main effects of psychological IPV exposure and possible exacerbation by broader social victimization (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Several studies reported positive associations between IPV and depression in the antenatal period (Flanagan et al, 2015;Paulson & Miller-Graff, 2019), postpartum period (Adynski et al, 2019;Agrawal et al, 2014;Escriba-Aguir et al, 2013;Jackson et al, 2015;Kita et al, 2019;McMahon et al, 2011;Valentine et al, 2011), or both (Flach et al, 2011;Ogbonnaya et al, 2013;Tiwari et al, 2008;Velonis et al, 2017;Woolhouse et al, 2012) even after adjusting for demographics, perinatal, or mental health factors. Five studies, however, found null associations between IPV (i.e., lifetime ¼ 3, recent ¼ 1, perinatal ¼ 1) and postpartum depression after adjusting for factors like childhood abuse and/or mental health (Dawson et al, 2019;Dennis & Vigod, 2013;Gaillard et al, 2014;Katon et al, 2014;Malta et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies reported positive associations between IPV and depression in the antenatal period (Flanagan et al, 2015;Paulson & Miller-Graff, 2019), postpartum period (Adynski et al, 2019;Agrawal et al, 2014;Escriba-Aguir et al, 2013;Jackson et al, 2015;Kita et al, 2019;McMahon et al, 2011;Valentine et al, 2011), or both (Flach et al, 2011;Ogbonnaya et al, 2013;Tiwari et al, 2008;Velonis et al, 2017;Woolhouse et al, 2012) even after adjusting for demographics, perinatal, or mental health factors. Five studies, however, found null associations between IPV (i.e., lifetime ¼ 3, recent ¼ 1, perinatal ¼ 1) and postpartum depression after adjusting for factors like childhood abuse and/or mental health (Dawson et al, 2019;Dennis & Vigod, 2013;Gaillard et al, 2014;Katon et al, 2014;Malta et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In the multilevel analyses, perinatal psychological IPV was not related to initial levels of postpartum mental health symptoms, nor the course of depression. It was, however, associated with a declining trajectory in PTSS (Dawson et al, 2019). Researchers also found that the effect of psychological IPV on mental health was moderated by gender discrimination, such that IPV predicted elevated depression and PTSS among women reporting high levels of gender discrimination.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations